2021
DOI: 10.3390/toxins13020161
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification and Toxin Analysis of Alexandrium spp. in the Beibu Gulf: First Report of Toxic A. tamiyavanichii in Chinese Coastal Waters

Abstract: The frequency of harmful algal blooms (HABs) has increased in China in recent years. Information about harmful dinoflagellates and paralytic shellfish toxins (PSTs) is still limited in China, especially in the Beibu Gulf, where PSTs in shellfish have exceeded food safety guidelines on multiple occasions. To explore the nature of the threat from PSTs in the region, eight Alexandrium strains were isolated from waters of the Beibu Gulf and examined using phylogenetic analyses of large subunit (LSU) rDNA, small su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This change in potency is advantageous to the mussels, as it results in a reduced total toxicity relative to molar concentration of toxin present. Different processes for toxin biotransformation include reduction, epimerization, oxidation, and desulfation [ 63 , 64 , 65 ]. The biotransformation potentially observed in this study resulted in the conversion to a less potent (C1+2) from a more potent (GTX1+4) form, which may be due to the epimerization process [ 66 ], and/or with the help of enzymes [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…This change in potency is advantageous to the mussels, as it results in a reduced total toxicity relative to molar concentration of toxin present. Different processes for toxin biotransformation include reduction, epimerization, oxidation, and desulfation [ 63 , 64 , 65 ]. The biotransformation potentially observed in this study resulted in the conversion to a less potent (C1+2) from a more potent (GTX1+4) form, which may be due to the epimerization process [ 66 ], and/or with the help of enzymes [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analgesia for 60 min was obtained with neosaxitoxin at 34 ± 2 micromol/L, saxitoxin at 58 ± 3 micromol/L, TTX at 92 ± 5 micromol/L, and decarbamoyl saxitoxin at 268 ± 8 micromol/L [89]. Wand et al in 2006 detected the presence of goyautoxins in ATGX02 strain of Alexandrium tamarense isolated near Weizhou Island in the Beibu Gulf [81], while Xu et al in 2021 found that Alexandrium tamiyavanichii isolated from Beibu Gulf waters in China produces low levels of saxitoxins and gonyautoxins [90]. The gonyautoxins are phycotoxins that act by reversibly blocking voltage-gated sodium channels at axonal levels.…”
Section: Possible Applicationsmentioning
confidence: 99%
“…In the coastal waters of China, about 11 Alexandrium species have been documented, including Alexandrium affine, Alexandrium andersonii, Alexandrium catenella, Alexandrium fraterculum, Alexandrium leei, Alexandrium minutum, Alexandrium ostenfeldii, Alexandrium pacificum, Alexandrium pseudogonyaulax, Alexandrium tamiyavanichii, and Alexandrium tamutum (Gu, 2011;Gu et al, 2013;Huang et al, 2021;Tang et al, 2021;Xu et al, 2021). In Chinese coastal waters, large-scale HABs caused by species of this genus have been reported frequently since 2000.…”
Section: Introductionmentioning
confidence: 99%